An evaluation of a safety improvement intervention in care homes in England: a participatory qualitative study. (November 2018) - Marshall, Martin; Pfeifer, Nadine; de Silva, Debi; Wei, Li; Anderson, James; Cruickshank, Lesley; Attreed-James, Kieran; Shand, Jenny
Summary: Objective: A growing proportion of older people live in care homes and are at high risk of preventable harm. This study describes a participatory qualitative evaluation of a complex safety improvement intervention, comprising training, performance measurement and culture-change elements, on the safety of care provided for residents. Design: A participatory qualitative study. Setting: Ninety care homes in one geographical locality in southern England. Participants: A purposeful sample of care home managers, front-line staff, residents, quality improvement facilitators and trainers, local government and health service commissioners, and an embedded researcher. Main outcome measures: Changes in care home culture and work processes, assessed using documentary analysis, interviews, observations and surveys and analysed using a framework-based thematic approach. Results: Participation in the programme appears to have led to changes in the value that staff place on resident safety and to changes in their working practices, in particular in relation to their desire to proactively manage resident risk and their willingness to use data to examine established practice. The results suggest that there is a high level of commitment among care home staff to address the problem of preventable harm. Mobilisation of this commitment appears to benefit from external facilitation and the introduction of new methods and tools. Conclusions: An evidence-based approach to reducing preventable harm in care homes, comprising an intervention with both technical and social components, can lead to changes in staff priorities and practices which have the potential to improve outcomes for people who live in care homes.